Mentoring in Higher Education: A Self Study of Faculty Socialization - Nancy Dubetz; Steve Turley (Networks: An Online Journal for Teacher Research, 2001)
Most professors typically have little formal preparation for their careers in academe and thus learn their craft by doing. Often those who seek support during this process look to experienced colleagues to mentor them. Mentoring, as experienced by most new faculty, tends to be individual, informal, and random. The role of the mentor for new faculty is often assumed by the department chair, though some junior faculty report that they use multiple mentors to help them with their varied responsibilities in teaching, scholarship, and university service. The mentor initiates the new faculty member into the customs and expectations of academic life, shares knowledge about the institution, and helps him/her establish an identity within the academic community. In this paper, we describe what we learned about mentoring through a self-study of our socialization into higher education.